1997
DOI: 10.1055/s-2007-972598
|View full text |Cite
|
Sign up to set email alerts
|

Administration of a GABABAgonist Baclofen Before Running to Exhaustion in the Rat: Effects on Performance and on Some Indicators of Fatigue

Abstract: The present study was designed to examine the effects of administration of a GABAergic agonist (Baclofen) on run-time to exhaustion in trained and untrained rats, and on some indicators of fatigue. Run-time to exhaustion on a treadmill set at a speed of 25 m.min-1 was significantly increased in both untrained (p < 0.01) and trained rats (p < 0.005) administered with baclofen one hour before the exercise. The animals who had run the longest time displayed the lowest concentrations of liver and muscle glycogen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…This effect may be related to the potential role of GABA in the occurence of fatigue. It has recently been shown that prolonged exercise decreases brain GABA concentration in the rat ( Chaouloff et al 1986 a) and that the administration of a GABA B agonist improves endurance time to exhaustion ( Abdelmaki et al 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be related to the potential role of GABA in the occurence of fatigue. It has recently been shown that prolonged exercise decreases brain GABA concentration in the rat ( Chaouloff et al 1986 a) and that the administration of a GABA B agonist improves endurance time to exhaustion ( Abdelmaki et al 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of the hypothesis is the assumption that only one neurotransmitter, 5-HT, can influence fatigue. This complexity is best exemplified by the observation that drugs that alter the concentrations of DA (Bhagat and Wheeler 1973a, b;Bracken et al 1988Bracken et al , 1989Cooter and Stull 1974;Derevenco et al 1981Derevenco et al , 1982Derevenco et al , 1986Gerald 1978;Heyes et al 1985;Kalinski et al 2001;Meeusen et al 1997a;Snider et al 1983;Trudeau et al 1990;Williams and Thompson 1973), nitric oxide (Lacerda et al 2006), norepinephrine (Jacobs and Bell 2004), adenosine (Davis et al 2003), and gamma-aminobutyric acid (GABA) (Abdelmalki et al 1997) can also influence fatigue. For example, administration of baclofen, a GABA B receptor agonist, can delay the onset of fatigue (Abdelmalki et al 1997), while 5 0 -N-ethylcarboxamidoadenosine, an adenosine receptor agonist, can hasten the onset of fatigue (Davis et al 2003) in rats.…”
Section: Brief Review Of the Role Of Monoamines In Central Fatiguementioning
confidence: 99%
“…There are several other transmitters and their subtypes that need to be examined for their role in central fatigue. For example, it is already known that brain gamma-aminobutyricacid (GABA) levels diminish with exercise (Gandevia, 2001) and that baclofen, a GABAergic agonist that acts on GABA B receptors, can postpone fatigue (Abdelmalki et al, 1997). Other humoral signals that must be considered to be involved in central fatigue are glutamine and ammonia, which are diminished and increased, respectively, after exercise (Gandevia, 2001).…”
Section: Central Nervous System Biochemical Changes and Central Fatiguementioning
confidence: 99%